PENGARUH HARGA, TEMPAT DAN PELAYANAN TERHADAP MINAT PENGGUNA JASA FOTOGRAFI (Studi Kasus Pada FZM Photography) - Firda Zahroh Maulia (AmaNU: Jurnal Manajemen dan Ekonomi, 2023)
This research is a survey research on photo users at FZM Photography located in Cilacap. This research takes the title: "The Effect of Price, Place and Service on User Interest in Photography Services (Case Study at Fzm Photography)". Based on the results of research and data analysis, it shows that: (1) Price has a negative effect on user interest, (2) Place has a negative effect on user interest, (3) Service Quality has a positive effect on user interest, (4) Price, Place and Service Quality have a positive effect on user interest. The implications of the above conclusions are: (1) Considering that service quality has an effect on user interest, it is recommended that the owner of FZM Photography should improve service quality. (2) Price and Place have no effect on user interest, the owner of FZM Photography should maintain the current price set and maintain the current place used. (3) Considering that the three variables of price, place and service quality have a joint influence on user interest in photo services at FZM Photography, the shop owner should maintain affordable prices in the future so that consumers continue to increase, then in terms of place and service quality the shop owner should also continue to maintain a better place and service quality.